การประเมินคุณภาพน้ำในแม่น้ำบางปะกงและชายฝั่งทะเลของจังหวัดชลบุรีในปี พ.ศ. 2563 โดยใช้วิธีดัชนีคุณภาพน้ำและภูมิสารสนเทศ - Majandang , Jiradech; Piyapong, Chantima (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2023)
Evaluation of Water Quality in Bangpakong River and Coastal Area of Chonburi Province in 2020 by Using Water Quality Index Method and Geoinformatics Jiradech Majandang and Chantima Piyapong รับบทความ: 8 เมษายน 2566; แก้ไขบทความ: 2 มิถุนายน 2566; ยอมรับตีพิมพ์: 11 มิถุนายน 2566; ตีพิมพ์ออนไลน์: 14 พฤศจิกายน 2566 บทคัดย่อ จากการประเมินคุณภาพน้ำในแม่น้ำบางปะกงและชายฝั่งทะเลของจังหวัดชลบุรีในปี พ.ศ. 2563 จากข้อมูลคุณภาพน้ำที่ตรวจวัดได้รวมกับข้อมูลที่เผยแพร่โดยกรมควบคุมมลพิษ กระทรวงทรัพยากรธรรมชาติและสิ่งแวดล้อม สำนักความปลอดภัยและสิ่งแวดล้อมทางน้ำ กรมเจ้าท่า กระทรวงคมนาคม และฝ่ายวิจัยวิทยาศาสตร์ทางทะเล สถาบันวิทยาศาสตร์ทางทะเล มหาวิทยาลัยบูรพา ด้วยวิธีดัชนีคุณภาพน้ำในแหล่งน้ำผิวดินและดัชนีคุณภาพน้ำทะเลและภูมิสารสนเทศ พบว่า พื้นที่ต้นน้ำมีคุณภาพน้ำอยู่ในเกณฑ์ดีและดีมากในทุกฤดู ตอนบนของแม่น้ำบางปะกงบริเวณพื้นที่รับน้ำจากชุมชนมีคุณภาพน้ำอยู่ในเกณฑ์เสื่อมโทรมถึงพอใช้ในฤดูร้อน และเกณฑ์พอใช้ถึงดีมากในฤดูฝนและฤดูหนาว ตอนล่างของแม่น้ำบริเวณพื้นที่เกษตรกรรมและการเพาะเลี้ยงมีคุณภาพน้ำอยู่ในเกณฑ์เสื่อมโทรมถึงพอใช้ในทุกฤดู ขณะที่คุณภาพน้ำในพื้นที่ปากแม่น้ำอยู่ในเกณฑ์เสื่อมโทรมในฤดูร้อน และเกณฑ์เสื่อมโทรมถึงพอใช้ในฤดูฝนและฤดูหนาว ส่วนคุณภาพน้ำในพื้นที่เพาะเลี้ยงสัตว์น้ำชายฝั่งทะเลอ่าวชลบุรีอยู่ในเกณฑ์พอใช้ถึงดีมากในฤดูร้อน เกณฑ์เสื่อมโทรมถึงดีในฤดูฝน และเกณฑ์พอใช้ในฤดูหนาว และคุณภาพน้ำในพื้นที่นันทนาการหาดบางแสนอยู่ในเกณฑ์พอใช้ถึงดีมากในฤดูร้อน เกณฑ์เสื่อมโทรมถึงดีมากในฤดูฝน และเกณฑ์พอใช้ถึงดีในฤดูหนาว ตามลำดับ การประเมินคุณภาพน้ำแสดงให้เห็นกิจกรรมในพื้นที่รับน้ำจากชุมชนและพื้นที่เกษตรกรรมและการเพาะเลี้ยงที่ส่งผลต่อคุณภาพน้ำที่ระบายผ่านปากแม่น้ำบางปะกงไปยังพื้นที่ชายฝั่งทะเลของจังหวัดชลบุรี คำสำคัญ: แม่น้ำบางปะกง การประเมินคุณภาพน้ำ ดัชนีคุณภาพน้ำ ภูมิสารสนเทศ Abstract There was the evaluation of water quality in Bangpakong River and coastal areas of Chonburi Province in 2020 from the measured water quality data combined with the published data: 1) Pollution Control Department, Ministry of Natural Resources and Environment 2) Bureau of Aquatic Safety and Environment, Marine Department, Ministry of Transport and 3) Research Division for Marine Science, Institute of Marine Science, Burapha University. Surface Water Quality Index (WQI) and Marine Water Quality Index (MWQI) and geoinformatics method were used to evaluate the water quality in these areas. The finding is the following. For the area of watershed, the water quality was good and very good in all the seasons. However, for the upstream of the Bangpakong river in the community catchment area, the water quality was poor to moderate in summer season, and it was moderate to excellent in rainy and winter seasons. For the downstream of the river in the area of agriculture and farming, the water quality was poor to moderate in all seasons. However, the water quality in the area of river mouth was poor in summer season and was poor to moderate in rainy and winter seasons. As for the area of coastal aquaculture along the coast of Chonburi Bay, the water quality was moderate to excellent in summer season, was poor to good in rainy season and was moderate in winter season. Finally, the water quality of the area of recreation in Bangsaen Beach was moderate to excellent in summer season, was poor to excellent in rainy season and was moderate to good in winter season, respectively. The water quality assessment shows that community activities and agricultural and aquaculture areas affect on the quality of water discharge through the Bangpakong Estuary to the coastal areas of Chonburi Province. Keywords: Bangpakong river, Assessment of water quality, Water quality index, Geoinformatics